2011
DOI: 10.1074/jbc.m111.220491
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin, a Novel Peroxisome Proliferator-activated Receptor γ (PPARγ) Target Gene That Promotes Mesenchymal Stem Cell Adipogenesis

Abstract: Chemerin is an adipocyte-secreted protein that regulates adipogenesis and the metabolic function of mature adipocytes via activation of chemokine-like receptor 1 (CMKLR1). Herein we report the interaction of peroxisome proliferator-activated receptor ␥ (PPAR␥) and chemerin in the context of adipogenesis. Knockdown of chemerin or CMKLR1 expression or antibody neutralization of secreted chemerin protein arrested adipogenic clonal expansion of bone marrow mesenchymal stem cells (BMSCs) by inducing a loss of G 2 /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(143 citation statements)
references
References 59 publications
8
126
1
8
Order By: Relevance
“…Previous research suggested that the physiologic role of PPARc2 is to regulate development of the adipose lineage in response to endogenous lipid activators and that this factor may serve to link the process of adipocyte differentiation to systemic lipid metabolism (Muruganandan et al 2011). So we have chosen the PPARc2 as an adipogenic differentiation marker of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggested that the physiologic role of PPARc2 is to regulate development of the adipose lineage in response to endogenous lipid activators and that this factor may serve to link the process of adipocyte differentiation to systemic lipid metabolism (Muruganandan et al 2011). So we have chosen the PPARc2 as an adipogenic differentiation marker of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A thymidine incorporation assay was used to analyze the serum-free or serum-induced proliferation of YFP-or YFP-NOS1APa-expressing cells as described previously (21,22). The incorporation of 1 Ci/ml radioactive [methyl-3 H]thymidine (Perkin-Elmer) into cellular DNA during a 15-min pulse time was quantified by liquid scintillation counting.…”
Section: Antibodiesmentioning
confidence: 99%
“…Several studies indicated altered chemerin levels or hepatic chemerin expression in chronic liver diseases of different origin, including NAFLD and chronic hepatitis C (CHC) [5,19,20,21,22,23,24,25]. Chemerin acts by binding the G protein-coupled receptor, chemokine receptor-like 1 (CMKLR1) (also known as chemerin receptor 23 (ChemR23)) [7,26], expressed by a variety of cells [26,27,28,29]. CMKLR1 was highly abundant in the liver and is expressed by primary human hepatocytes, hepatic stellate cells, Kupffer cells, and bile duct cells [30].…”
Section: Introductionmentioning
confidence: 99%